Impulse Buying and the Mediating Role of Positive Emotion - Supriatno, Gun Gun; Pratminingsih, Sri Astuti (Jurnal E-Bis, 2025)
The beauty industry in Indonesia continues to grow in line with the increasing use of e-commerce, particularly among Generation Z. This phenomenon has led to the rise of impulsive buying behavior influenced by hedonic motives and digital promotions such as flash sales. This study examines the influence of hedonic consumption and flash sales on impulse buying among Generation Z in West Java, with positive emotion as a mediating variable. A quantitative approach was employed with data collected from 160 purposively sampled respondents through a Likert-scale questionnaire. Data were analyzed using multiple linear regression and the Sobel test in SPSS 25. Findings indicate that both hedonic consumption and flash sales positively and significantly affect impulse buying, directly and indirectly through positive emotion. The study contributes to understanding how emotional responses reinforce digital marketing strategies in the Indonesian beauty industry.